2020
DOI: 10.1111/lnc3.12368
|View full text |Cite
|
Sign up to set email alerts
|

Research methods in articulatory phonetics I: Introduction and studying oral gestures

Abstract: This article is Part I of a general overview of current methods in articulatory phonetics research. This part deals with methods used to investigate oral gestures—speech‐related movements of the tongue, the lips, and the jaw (while Part II is concerned with methods studying laryngeal and nasal gestures, and the entire vocal tract). The focus of the article is on electropalatography, ultrasound, and electromagnetic articulography, with some attention also given to static palatography, X‐ray microbeam, and video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 115 publications
1
5
0
Order By: Relevance
“…Our literature review (see description below) showed that around 75% of studies published in journals included ten participants or fewer; around 46% included five participants or fewer. This is also in line with Kochetov (2020), who reported the median number of participants in an EMA study to be five. Early studies (e.g., earlier than 2003) have often only included one or two participants, and it was not uncommon for one of the authors to be a participant.…”
Section: Participantssupporting
confidence: 89%
“…Our literature review (see description below) showed that around 75% of studies published in journals included ten participants or fewer; around 46% included five participants or fewer. This is also in line with Kochetov (2020), who reported the median number of participants in an EMA study to be five. Early studies (e.g., earlier than 2003) have often only included one or two participants, and it was not uncommon for one of the authors to be a participant.…”
Section: Participantssupporting
confidence: 89%
“…We recorded 11 participants (9 female and 2 male). (Note: Because articulometry experiments are long and demanding, worldwide median participant counts are small (5 as of 2020 44 ). All but one of the participants were native monolingual North American English (NAE) speakers, and the other was a native bilingual NAE and French speaker.…”
Section: Methodsmentioning
confidence: 99%
“…Our data come from four female speakers, two from France (FE1: Clermont-Ferrand, FE2: Cherbourg) and two from Quebec, Canada (FQ1: Chicoutimi, FQ2: St-Jean-sur-Richelieu). While small, the number of speakers involved in this study is in keeping with previous EPG research, for which the median sample size is four participants per study (Kochetov, 2020, based on a review of 54 EPG studies published between 2000and 2019.…”
Section: Participantsmentioning
confidence: 99%